Joint ventures in construction 2: contract, governance, performance and risk - Kobayashi, Kiyoshi (ICE Publishing, Thomas Telford, 2012)
Joint Ventures in Construction 2: Contract, Governance, Performance and Risk is the selected proceedings of a series of International Conferences on Multi-national Joint Ventures for Construction Works, held each year since 2005. This book brings together the highlights from the 2008-2011 conferences, focusing on key issues including - contract and associated administrative structures - governance, dispute, and dispute resolution - performance and risk - managing stakeholder expectations.